Potential of Utilizing Arabika Coffee Dregs (Coffea Arabica L.) as Biochar for Increasing Fertility of Plant Media - Kabul Warsito; Nur Asmaq; Indra Irawan; Namira Sinarta Purba; Johan Heinze (The International Conference on Education, Social Sciences and Technology (ICESST), 2023)
Coffee dregs biochar is an organic material that contains lots of nutrients for increasing soil fertility. The nutrient content in biochar is very good for plant growth. Research about the use of biochar from arabica coffee dregs (Coffea arabica L.) has been done to know its effectiveness in increasing the fertility of the planting medium. This research used a completely random design with a combination treatment consisting of 4 planting media mixtures. Treatment P 0 = Biochar: Compost coffee skin: Top Soil (0: 1: 2); P 1 = Biochar: Compost coffee skin: Top Soil (1: 1: 2); P 2 = Biochar: Compost coffee skin: Top Soil (1: 0: 2); P 3 = Biochar: Compost coffee skin: Top Soil (2: 1: 2); P4 = Biochar: Compost coffee skin: Top Soil (1: 2: 2); P5 = Biochar: Compost coffee skin: Top Soil (1: 1: 1). In the growth of Arabica coffee bud, treatment P1 showed best results at observation height plants (7.8 cm). Treatment P3 showed the best results at observation of total leaves (2.9). Treatment P1 showed the best results in the observation of leaves area (85.2 mm) and treatment P4 showed the best results in observing of stem diameter (2.4 mm). Treatment P1 also showed the best results for observation of wet weight (32.2 g) and dry weight (9.76 g). However, the control treatment showed best results on roots wet weight (7.41 g) and roots dry weight (2.07 g). Analysis results in nutrient content in processed coffee dregs biochar activated with coenzymes showed content element N: 1.45%; P: 223.45 mg; K: 3.54 mg; Ca: 21.78 mg; Mg: 2.56 mg. After the biochar is mixed with compost coffee skins and topsoil enhancement of nutrient content. Treatment combination is best shown by treatment P3 where element rate the highest elements N, P, K, Ca, and Mg compared to treatment other. Results showed that biochar combined in several types of planting medium is effective in increasing the fertility of the planting medium.